2012
DOI: 10.2337/db11-1729
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptor Kinase 2, With β-Arrestin 2, Impairs Insulin-Induced Akt/Endothelial Nitric Oxide Synthase Signaling in ob/ob Mouse Aorta

Abstract: In type 2 diabetes, impaired insulin-induced Akt/endothelial nitric oxide synthase (eNOS) signaling may decrease the vascular relaxation response. Previously, we reported that this response was negatively regulated by G protein–coupled receptor kinase 2 (GRK2). In this study, we investigated whether/how in aortas from ob/ob mice (a model of type 2 diabetes) GRK2 and β-arrestin 2 might regulate insulin-induced signaling. Endothelium-dependent relaxation was measured in aortic strips. GRK2, β-arrestin 2, and Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 30 publications
3
71
0
Order By: Relevance
“…For gene silencing assay, small interfering RNA (siRNA) specifically targeting GRK2 mRNA was purchased from Santa Cruz Biotechnology. Arteriolar tissues were transfected with siRNA specific to GRK2 or scrambled control by Lipofectamine 2000 (Invitrogen, Carlsbad, CA) following the manufacturer's instructions (29,33). At 48 h after transfection, arteriolar segments were treated with 10 Ϫ7 M insulin for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For gene silencing assay, small interfering RNA (siRNA) specifically targeting GRK2 mRNA was purchased from Santa Cruz Biotechnology. Arteriolar tissues were transfected with siRNA specific to GRK2 or scrambled control by Lipofectamine 2000 (Invitrogen, Carlsbad, CA) following the manufacturer's instructions (29,33). At 48 h after transfection, arteriolar segments were treated with 10 Ϫ7 M insulin for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…15,16,27) Briefly, the thoracic aortas were carefully isolated from mice, dissected from surrounding fat and connective tissue, cut into circular segments (2 mm long), and immediately placed in Krebs-Henseleit Solution (KHS), concentration in mmol/L: NaCl, 118.0; KCl, 4.7; NaHCO 3 , 25.0; CaCl 2 , 1.8; NaH 2 PO 4 , 1.2; MgSO 4 , 1.2; glucose, 11.0. Aortic rings were suspended in 10 mL jacketed organ baths filled with 10 mL of KHS continuously aerated with a mixture of 95% O 2 and 5% CO 2 at 37°C.…”
Section: Measurement Of Isometric Forcementioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16]27,28) Plasma samples were stored at −20°C until analysis. Briefly, plasma glucose, cholesterol, high-density lipoprotein (HDL) cholesterol, triglyceride, and serum non-esterified fatty acid (NEFA) levels were each determined with a commercially available enzyme kit (Wako Pure Chemical Industries, Ltd., Osaka, Japan).…”
Section: Ca Mo and Rv Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Translocation of G protein-coupled receptor kinase 2 to the plasma membrane interferes with β-arrestin 2-mediated activation of the Akt/eNOS pathway in the ob/ob mouse aorta. 36 Moreover, Fernández-Hernando et al reported that genetic ablation of Akt1 on an apolipoprotein E knockout background (ApoE -/-Akt1 -/-) increases aortic lesion expansion and promotes coronary atherosclerosis relative to ApoE -/-single nulls. 37 Akt1 loss increases the levels of inflammatory mediators and reduces eNOS phosphorylation.…”
Section: Effect Of Chronic Sa4503 Treatment On Akt Phosphorylation Inmentioning
confidence: 99%